Bogatyri - Vasnetsov, Viktor (Академия художеств СССР (Academy of Arts of the USSR), 1952)
Artwork; Bogatyrs in field 1952 reproduction of painting (c.1881-1898) 'Bogatyri' from Russian artist Viktor Vasnetsov. Original title: Богатыри PO-1191